2014
DOI: 10.1128/aem.00551-14
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Distribution and Distinctive Variations of Cylindrospermopsin Genes in Cyanobacterial Strains and Environmental Samples from Chinese Freshwater Bodies

Abstract: e Increasing reports of cylindrospermopsins (CYNs) in freshwater ecosystems have promoted the demand for identifying all of the potential CYN-producing cyanobacterial species. The present study explored the phylogenetic distribution and evolution of cyr genes in cyanobacterial strains and water samples from China. Four Cylindrospermopsis strains and two Raphidiopsis strains were confirmed to produce CYNs. Mutant cyrI and cyrK genes were observed in these strains. Cloned cyr gene sequences from eight water bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…The findings of the saxitoxin ( sxt ) gene in Harsha Lake samples indicated the potential production of this neurotoxin of A. circinalis and Aphanizomenon sp. As for Cylindrospermopsis , the sequences observed in this study were similar to the isolate sequences from Chinese waters like Xihu Lake, Qiandun Lake and Qingdao pond, which mostly revealed no presence of toxic genes ( cyrA and cyrL ) [19]. However, rpoC based genotypes might not necessarily indicate whether Cylindrospermopsis showed cyr gene positive, considering rpoC gene presented in both toxic and nontoxic species, while the cyr gene was found to sporadically distribute in cyanobacterial strains and environmental samples [19].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The findings of the saxitoxin ( sxt ) gene in Harsha Lake samples indicated the potential production of this neurotoxin of A. circinalis and Aphanizomenon sp. As for Cylindrospermopsis , the sequences observed in this study were similar to the isolate sequences from Chinese waters like Xihu Lake, Qiandun Lake and Qingdao pond, which mostly revealed no presence of toxic genes ( cyrA and cyrL ) [19]. However, rpoC based genotypes might not necessarily indicate whether Cylindrospermopsis showed cyr gene positive, considering rpoC gene presented in both toxic and nontoxic species, while the cyr gene was found to sporadically distribute in cyanobacterial strains and environmental samples [19].…”
Section: Discussionsupporting
confidence: 61%
“…As for Cylindrospermopsis , the sequences observed in this study were similar to the isolate sequences from Chinese waters like Xihu Lake, Qiandun Lake and Qingdao pond, which mostly revealed no presence of toxic genes ( cyrA and cyrL ) [19]. However, rpoC based genotypes might not necessarily indicate whether Cylindrospermopsis showed cyr gene positive, considering rpoC gene presented in both toxic and nontoxic species, while the cyr gene was found to sporadically distribute in cyanobacterial strains and environmental samples [19]. Currently HAB monitoring using microscopy for phytoplankton and analytical analysis for cyanotoxin is recommended by local agencies such as OH EPA in their State of Ohio Harmful Algal Bloom Response Strategy For Recreational Waters [7].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The toxin profile of C. raciborskii appears to be diversified in relation to the geographical zone . In general, CYN-producing strains occur in Australia and Asia (Jiang et al, 2014), whereas strains capable of saxitoxins (neurotoxic alkaloids) production are found in South America (Hoff-Risseti et al, 2013). African and European strains have not been shown to produce any known cyanotoxin (Haande et al, 2008; although the crude extracts of the latter were demonstrated to exhibit potentially toxic properties (Antal et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The Chinese cylindrospermopsin‐producing strains were shown to retain the cyrN and cyrO genes within the aforementioned hyp locus, whereas strains lacking the cyr gene cluster contained the cyrO gene at this position. Taken together this suggests that cyrO was present prior to the initial acquisition of the cluster (Jiang et al ., ) and that cyrN within this region can be viewed as a marker of strains that have acquired the cluster at some point and have subsequently lost or translocated the operon. The varying arrangement of the cyr gene cluster, and the replacement with the saxitoxin ( sxt ) gene cluster within geographically distant strains of the Cylindrospermopsis/Raphidiopsis complex, raises a number of questions regarding the timing of these recombination events.…”
Section: Genomicsmentioning
confidence: 99%